The first case of esophageal mediastinal fistula after immunotherapy for non-small cell lung cancer: case report and literature review - Tianxiao Fu; Jiu Chen; Bing Xiong; Guolin Wu (Journal of Cardiothoracic Surgery)
Abstract Background Malignant esophageal mediastinal fistula is a severe complication that occurs in both the advanced stages of esophageal cancer and after radiotherapy for esophageal cancer. Esophageal mediastinal fistula is very susceptible to complications such as mediastinitis and mediastinal abscess, resulting in a significantly elevated mortality rate for patients. We reported a rare case of esophageal mediastinal fistula after immunotherapy for non-small cell lung cancer (NSCLC). Case Presentation A 74-year-old male patient with NSCLC was hospitalized in July 2023. About one week after Tislelizumab immunotherapy, the patient suddenly developed high fever accompanied by coughing and choking on water, chest tightness, shortness of breath, and hemoptysis. Following the completion of bronchial artery computed tomography angiography (CTA), imaging suggested the presence of esophageal mediastinal fistula. We opted for a conservative medical treatment instead of surgery. The patient was discharged without any complications. Conclusions This is the first case of NSCLC accompanied by an esophageal mediastinal fistula after treatment with tislelizumab. The occurrence of malignant esophageal mediastinal fistula is very uncommon and poses a high level of hazard. In addition, this paper provides a concise overview of cases of lung cancer complicated with esophageal fistula in the past 10 years. It offers valuable insights for diagnosis and treatment, serving as a resource for clinicians.